2022
DOI: 10.3233/jpd-212769
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Medication Burden in Parkinson’s Disease Outpatients

Abstract: Background: Individuals with Parkinson’s disease (PD) may be especially vulnerable to future cognitive decline from anticholinergic medications. Objective: To characterize anticholinergic medication burden, determine the co-occurrence of anticholinergic and cholinesterase inhibitors, and to assess the correlations among anticholinergic burden scales in PD outpatients. Methods: We studied 670 PD outpatients enrolled in a clinic registry between 2012 and 2020. Anticholinergic burden was measured with the Anticho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In two studies using ACB, 15.5-18.5% of patients had more than 2 points and 41.5-46.3% took at least one anticholinergic drug; these seem to be similar results to those in our study [42][43][44]. Geriatric patients from the same area of Poland hospitalised in a geriatric ward had a lower anticholinergic burden (ACB ≥ 3 13.98%, ACB ≥ 1 40.73%) than PD patients from our study, which might suggest that the topic is especially relevant for PD patients [45].…”
Section: Discussionsupporting
confidence: 89%
“…In two studies using ACB, 15.5-18.5% of patients had more than 2 points and 41.5-46.3% took at least one anticholinergic drug; these seem to be similar results to those in our study [42][43][44]. Geriatric patients from the same area of Poland hospitalised in a geriatric ward had a lower anticholinergic burden (ACB ≥ 3 13.98%, ACB ≥ 1 40.73%) than PD patients from our study, which might suggest that the topic is especially relevant for PD patients [45].…”
Section: Discussionsupporting
confidence: 89%
“…As the commonly used medicines, traditional anticholinergic drugs, such as trihexyphenidyl hydrochloride, amantadine, and levodopa preparations, have been found to exert serious side effects. Among them, the discomfort caused by the patient’s gastrointestinal tract is the most common, namely indigestion, vomiting, and constipation ( Sheu et al, 2019 ; Nawaz et al, 2022 ). Until now, none of therapies have been convincingly shown to slow down or prevent the progression of PD.…”
Section: Introductionmentioning
confidence: 99%
“…Periplaneta Americana ( P. Americana ), commonly known as the cockroach, has been a noted traditional Chinese medicinal material for thousands of years ( Ma et al, 2018 ). Studies showed that the P. Americana , which is widely distributed in tropical areas, contains a variety of small molecule peptides and amino acids, polysaccharides, oligosaccharides, clusterins, pheromones, and other components, which can promote tissue repair, enhance myocardial contractility, protect liver and resist damage, and improve immunity ( Sheu et al, 2019 ; Nawaz et al, 2022 ). According to the results of preliminary research in the laboratory ( Lu et al, 2021 ), researchers verified that the oligosaccharides extracted from the dregs of P. Americana (OPA), which were composed of 83% glucose, 11% xylose and 6% galactose, could effectively improve enteritis of model mice and demonstrated certain antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that approximately 81.3% of patients with PD receiving ACHEIs had a history of concurrent use of anticholinergics, and 45% were treated with high-potency anticholinergics. Another study with 670 PD outpatients enrolled in a clinic registry in the US between 2012 and 2020, reported that 5.4% of the study cohort were co-prescribed cholinesterase inhibitors and medications with anticholinergic properties [10]. Bayón and Sampedro analysed the use of inappropriate treatments in 500 patients with cognitive decline [11].…”
Section: Introductionmentioning
confidence: 99%